Vitamin D3 Supplementation Attenuates Surgery-Induced Neuroinflammation and Cognitive Impairment by Regulating NLRP3 Inflammasome in Mice - Jingyan Jiang; Xin Huang; Xiang Gao; Shenghui Yu (Mediators of Inflammation)
Neuroinflammation plays a dominant role in the progression of postoperative cognitive dysfunction (POCD). Vitamin D has been known to have important regulatory functions in inflammation and immune response. The NOD-like receptor protein 3 (NLRP3) is an essential inflammasome in the inflammatory response and could be activated by anesthesia and surgery. In this study, male C57BL/6 mice aged 14–16 months were given VD3 for 14 days straight before having an open tibial fracture surgery. The animals were either sacrificed to obtain the hippocampus or tested in a Morris water maze test. Western blot was employed to estimate the levels of NLRP3, ASC, and caspase-1, immunohistochemistry was used to identify microglial activation, and an enzyme-linked immunosorbent assay was used to measure the expression of IL-18 and IL-1β, while using the corresponding assay kits to assess ROS and MDA levels to reflect the oxidative stress status. We showed that VD3 pretreatment significantly improved surgery-induced memory and cognitive dysfunctions in aged mice, which was linked to the inactivation of the NLRP3 inflammasome and the inhibition of neuroinflammation. This finding provided a novel preventative strategy for clinically reducing postoperative cognitive impairment in elderly surgical patients. This study has some limitations. Gender differences in the effects of VD3 were not considered, and only male mice were used. Additionally, VD3 was given as a preventative measure; however, it is unknown whether it has any therapeutic benefits for POCD mice. This trial is registered with ChiCTR-ROC-17010610.